The Usage of Synthetic Wood Analysis as an Alternative Material in Kudus Traditional Houses - putri, vivi kurnia (Universitas Indraprasta PGRI, 2025)
Kudus traditional houses are known as houses that have distinctive architectural features using teak wood as the primary material. However, the availability of teak wood is increasingly scarce due to continuous exploitation. In contrast, the growth of teak wood takes a long time until it is ready to be harvested and utilized as material. The constant exploitation of teak wood can affect global warming due to reducing forests as carbon sinks. On the other hand, global warming also impacts the durability of teak wood, which is the primary material in traditional Kudus houses, making it more resistant to damage. This condition requires high maintenance and maintenance costs, causing the number of Kudus traditional houses to decrease. In overcoming the dependence on teak materials in Kudus traditional houses, there is a need for a material strategy that can be used sustainably. This research explores sustainable strategies in using Kudus traditional house materials by replacing teak wood with synthetic wood, which is more readily available at a relatively cheaper price. This research method uses a qualitative approach with field observations and literature studies regarding teak materials. The results showed that several types of synthetic wood have the potential to replace teak wood in terms of durability, aesthetics, and environmental sustainability. Using synthetic wood can solve the scarcity of teak wood without sacrificing the cultural value of traditional Kudus houses. This research shows that adopting synthetic materials can effectively preserve traditional architecture while supporting sustainable development.